Poverty alleviation strategies of NGOs - Rajasekhar, D. (New Delhi, 2004)
This study examines the efforts made by the NGOS in alleviating poverty, with special reference to India. Analysing the magnitude and severity of poverty and the process generating poverty, it makes an assessment of efforts made by line departments, panchayati raj institutions at the village level and other agencies such as banks and credit co-operatives. It also evaluates the strategies adopted by the poor in coming out of poverty. The book will be of great use for researchers, policy makers, development activists and the NGOS.
Keywords: Poverty